Citra Dan Peranan Perempuan Dalam Novel Tenaga Kerja Istimewa Karya Naiqueen: Tinjauan Feminisme Dan Implementasinya Sebagai Materi Pembelajaran Sastra Di SMP - Fahmawati, Fatikhah, Drs. Adyana Sunanda, M.Pd (2016)
ABSTRACT The aims of this research are to identify, (1) the structures of the Tenaga Kerja Istimewa novel by Naiqueen, (2) to describe the image andthe act of woman in the Tenaga Kerja Istimewa novel, and (3) the implementation of theresult as a material of teaching learning process in SMP. This research used descriptive qualitative method. The objects of this research are the image and the act of woman. The data in this research is paragraphs in the Tenaga Kerja Istimewa novel. The data source of this research is found in the Tenaga Kerja Istimewa novel. The techniques to collect the data are literature and record. The data validity in this research is the researcher triangulation. The technique to analyze the data used hermeneutic method. Based on the research, there are three results, (1) the structures of the Tenaga Kerja Istimewa novel are the characters consist of Annisa Cahyawulan and Pangeran Yousoef, the plot is progressive, and took the places in Jeddah, Saudi Arabia and London, England as long as a half year, and the theme of this novel is human, (2) the image and the act of woman consists of a hard worker, as a wife, perseverance and autonomous, and the last is a good personality as Annisa Cahyawulan as the main character, (3) the result of this research is with the literature education of the VIII class in the first semester as SK 7 KD 7.1 in KTSP curriculum. Keywords: Novel, the image and the act of woman, Feminism.